NORTH CAROLINA DEPARTMENT OF HEALTH AND HUMAN SERVICES, A FIELD EXPERIENCE - Bedenberg, Ashley (My University, 2014)
This report presents a field experience of 240 hours completed in the North Carolina Department of Health and Human Services, Communicable Disease Branch. The Communicable Disease Branch protects the public’s health by facilitating communication among local, state and federal health agencies including physicians, local health department staff and hospital and occupational infection control personnel. They also play an active role in real-time surveillance for the state by monitoring International Coding Data input from hospital emergency departments, the Carolinas Poison Control Center, ambulance calls and some urgent care facilities in a program called the North Carolina Disease Event Tracking and Epidemiologic Collection Tool (NC DETECT). Reporting is monitored through The North Carolina Electronic Disease Surveillance System (NC EDSS) that is part of The Centers for Disease Control’s initiative to move to electronic-based reporting. My time as an intern in the Communicable Disease Branch was spent exploring and experiencing the work of public health professionals through participation in activities of the branch in addition to various other agencies and departments. My completed projects include a guidance document for Animals in Public Settings in North Carolina, an updated Rabies Sample Submission Questionnaire, a PowerPoint for the use in teaching young school age children to stay safe around dogs, and a two page summary of what I have learned about public health practice at North Carolina Department of Health and Human Services. My participation in the activities of the Communicable Disease Branch and related agencies broadened my knowledge of public health by experiencing the role the various agencies play in contributing to the health of the community.
Keywords: North Carolina; Communicable disease; Rabies; Public Health (0573)